Etika kerja islam, kecerdasan emosional, dan dukungan organisasi dalam meningkatkan kinerja karyawan: Peran mediasi komitmen organisasi - Laili, Alfi Nur Laili; Pratama, Abdul Aziz Nugraha (Kurva: Jurnal Ekonomi Manajemen Keuangan dan Bisnis, 2024)
In human-centered service organizations, effectiveness largely depends on system integration and the quality of human resource management. Dynamic organizations continuously strive to enhance productivity and maintain competitive advantage through consistent performance. This study aims to analyze the influence of Islamic work ethics, emotional intelligence, and organizational support on employee performance, with organizational commitment as a mediating variable. The research was conducted at PKU Muhammadiyah Hospital Wonosobo using questionnaires distributed to 85 respondents selected through purposive sampling. Data were analyzed using the path analysis approach. The results show that Islamic work ethics and organizational support have a positive and significant effect on employee performance, while emotional intelligence does not. Islamic work ethics and organizational support also significantly increase organizational commitment. However, commitment does not have a significant effect on performance and does not act as a mediating variable. These findings highlight the importance of strengthening work values and direct organizational support to enhance employee performance in high-pressure work environments.